Is Septoplasty Necessary When Using the Endoscopic Endonasal Transsphenoidal Approach for a Deviated Nasal Septum? - Kim, Do Hyun; Hong, Yong-Kil; Jeun, Sin-Soo; Park, Jae-Sung; Kim, Soo Whan; Cho, Jin Hee; Park, Yong Jin; Kim, Seon Ik; Kim, Sung Won (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective This article describes the role played by endoscopic endonasal transsphenoidal approach (EETSA) to the sphenoidal process of the septal cartilage of a deviated nasal septum.Design Case series with chart review.Setting Tertiary referral center.Participants Between 2009 and 2016, 177 patients with skull base tumors who underwent EETSA were included.Main Outcome Measures In 8 cases, the conventional two nostrils–four hands technique was employed (group A). In 16 cases, we placed a right-side conventional nasoseptal flap and a left-side modified nasoseptal rescue flap (group B), and in 153 cases, bilateral modified nasoseptal rescue flaps (group C). The number of septoplasty-required cases and the change of nasal cavity area differences reflecting septal deviation were measured.Results Septoplasty during EETSA was performed in two cases: one from group B and one from group C. There was no significant difference in the ratio of septoplasty-required cases among the three groups (p = 0.127). Between pre- and postoperative nasal cavity, the cross-sectional area difference at the anterior end of the middle turbinate level significantly decreased (p = 0.045). Also, the angle of deviation at the level of ostiomeatal unit significantly decreased after EETSA (p < 0.001).Conclusion Separation of a deviated complex surrounding the sphenoidal process of the septal cartilage is the key to relieving a deviated nasal septum. EETSA combined with the two nostrils–four hands technique allows posterior septectomy (including removal of this deviated complex) to be performed. Thus, EETSA may commence without preceding septoplasty even in cases with severe nasal septum deviations.
Keywords: septoplasty; sphenoidal process; endoscopic; endonasal; transsphenoidal